# Proving $A \triangle B = \varnothing \iff A =B$

Let A and B be subsets of a universe V.

I need to prove the following statement:

(I can't use associativity of symmetric difference)

$A \triangle B = \varnothing \iff A =B$

Here is my proof, could someone please check it and see if it's correct?

$A \triangle B = \varnothing \iff (A - B) \cup (B-A) = \varnothing$

$\iff (A \cap B^c)\cup(B \cap A^c) = \varnothing$

If $(A \cap B^c)$ is equal to a non-empty subset C, then $(A \cap B^c)\cup(B \cap A^c) = C \cup (B \cap A^c) \ne \varnothing$.

If $(B \cap A^c)$ is equal to a non-empty subset C, then $(A \cap B^c)\cup(B \cap A^c) = (A \cap B^c)\cup C \ne \varnothing$.

Therefore we have:

$(A \cap B^c)\cup(B \cap A^c) = \varnothing \iff (A \cap B^c) = \varnothing \land (B \cap A^c) = \varnothing$ (1)

Let $A = B$, so $A \cap B^c = B \cap A^c = A \cap A^c = B \cap B^c = \varnothing$, which means that:

$A = B \implies (A \cap B^c) = \varnothing \land (B \cap A^c) = \varnothing$ (2)

Assuming $A \ne B$, at least one of the following conditions holds:

(i). There exists an element x, such that $x \in A$ and $x \notin B$

(ii). There exists an element x, such that $x \notin A$ and $x \in B$

If (i) is true:

$\exists x \in (A \cap B^c) \implies (A \cap B^c) \ne \varnothing$ (3)

If (ii) is true:

$\exists x \in (B \cap A^c) \implies (B \cap A^c) \ne \varnothing$ (4)

By (1),(2),(3), and (4): $A \triangle B = \varnothing \iff A =B$

$\blacksquare$

• You have a slight error in the lines leading up to $(1)$. You treated the case were $(A\cap B^c)\neq \emptyset$ and $(B\cap A^c)=\emptyset$ as well as the case where $(B\cap A^c)\neq \emptyset$ and $(A\cap B^c)=\emptyset$ but you have not yet touched the case where $(A\cap B^c)$ and $(B\cap A^c)$ are simultaneously nonempty. Instead of adding a third case to consider, simply remove the second conditions in each case, i.e. remove the "and $(B\cap A^c)=\emptyset$" from the first line and similarly for the second. – JMoravitz Sep 21 '17 at 21:16
• I've edited the proof considering your correction in this comment. Is it correct now? – IMK Sep 21 '17 at 21:31
• Yes, though it might be worth writing as $(A\cap B^c)\cup (B\cap A^c)\supseteq C\supsetneq \emptyset$. There is nothing inherently incorrect about your steps (2) through (4) that I personally noticed, but I found them a bit hard to follow at times in trying to make sure that you were proving both directions of the if and only if. – JMoravitz Sep 21 '17 at 21:34

Apart from the one small mistake I pointed out in the comments above (you did not consider $(A\cap B^c)$ and $(B\cap A^c)$ both being nonempty simultaneously leading up to (1)), your proof is correct but could be cleaned up considerably.

Leading up to (1) you successfully proved that $A\triangle B=\emptyset\iff (A\cap B^c)=(B\cap A^c)=\emptyset$

I would have instead continued by showing $(A\cap B^c)=\emptyset\iff A\subseteq B$.

Let $x\in A$. Then since if $x\notin B$ would imply that $x\in A\cap B^c=\emptyset$, either the assumption that there existed an $x\in A$ at all or the assumption that $x\notin B$ must be incorrect. It follows then that $x\in B$ or that $A=\emptyset$, in either case $A\subseteq B$. Conversely, if $A\cap B^c\neq \emptyset$ then there must be some $x$ for which $x\in A$ and $x\notin B$, which would act as a counterexample to $A$ being a subset of $B$.

The same logic will show $(B\cap A^c)=\emptyset \iff B\subseteq A$.

As $(A=B)\iff (A\subseteq B)\wedge (B\subseteq A)$, we now have a chain of iff statements that prove the desired result.

For sets $A$ and $B$, $A\triangle B=\emptyset$ implies $$A=A\triangle \emptyset = A\triangle (A\triangle B)=(A\triangle A)\triangle B=\emptyset\triangle B=B\,.$$ The converse is trivial.

• I'm sorry. I forgot to write that I haven't proved yet that the symmetric difference is associative. So I can't use this. – IMK Sep 21 '17 at 21:26
• @IMK There is a very easy proof of the associativity of $\Delta$. – Batominovski Sep 21 '17 at 22:08

So you have to prove : $A \triangle B = \varnothing \iff A =B$

If $A=B$ then $(A - B)=\varnothing$ and $(B - A)=\varnothing$ so $(A - B) \cup (B-A)=\varnothing \cup \varnothing=\varnothing$

If $A \triangle B = \varnothing$ then $(A - B) \cup (B-A)=\varnothing$. If $A$ and $B$ are disjoint and both non-empty then $A-B$ and $B-A$ are non-empty so $(A - B) \cup (B-A)\neq \varnothing$. If one of them is empty and the other is not then either $A-B \neq \varnothing$ or $B-A \neq \varnothing$ so $(A - B) \cup (B-A)\neq \varnothing$. If both are empty then $A=B= \varnothing$.

If they are not disjoint then $A-B$ and $B-A$ are not both empty except in the case $A=B$ when they are both empty.